Increased prostacyclin levels inhibit the aggregation and activation of platelets via the PI3K–AKT pathway in prolonged isolated thrombocytopenia after allogeneic hematopoietic stem cell transplantation. Issue 139 (March 2016) - Zhang, Xiao-Hui; Zhou, Shi-Yuan; Feng, Ru; Wang, Ya-Zhe; Kong, Yuan; Zhou, Yi; Zhang, Jia-Min; Wang, Min; Zhao, Jing-Zhong; Wang, Qian-Ming; Feng, Fei-Er; Zhu, Xiao-Lu; et al.
Abstract: Objectives: The aim of this study was to investigate the role of prostacyclin (PGI2 ) in prolonged isolated thrombocytopenia (PT) following allogeneic hematopoietic stem cell transplantation (allo-HSCT) and the effect of PGI2 on the activation and aggregation of platelets in PT. Methods: We enrolled 37 patients with PT and 36 controls following allo-HSCT in this study. Platelet aggregation and activation and PGI2 levels were measured. Endothelial progenitor cells (EPCs) from either PT or control patients were cultured ex vivo with serum from either PT or control patients. PGI2 secretions were then measured. PGI2 was added to the platelets ex vivo, and platelet aggregation and activation and PI3K/Akt phosphorylation were analyzed. Results: A higher PGI2 level was observed in the PT patients. The activation and aggregation of platelets were significantly lower in the PT patients. EPCs from PT patients cultured in PT serum secreted higher levels of PGI2, and PGI2 inhibited platelet activation and aggregation in a concentration-dependent manner ex vivo . PI3K/Akt phosphorylation of platelets was regulated by PGI2 after allo-HSCT. Disease status, serum PGI2 level and platelet aggregation were independent risk factors in patients with PT after allo-HSCT. Conclusions: Higher PGI2 levels and lower platelet activation and aggregation occurred simultaneously in PT patients. PGI2 inhibited platelet activation and aggregation, probably by regulating the phosphorylation of PI3K/Akt. Highlights: PGI2 levels in serum were significantly increased in PT. Platelet aggregation and activation were significantly decreased in PT. PGI2 secreted by EPC was enhanced in PT ex vivo . Iloprost inhibited the aggregation of platelets through PI3K/Akt pathway ex vivo .